Ageing coefficient for early age tensile creep of blended slag and low calcium fly ash geopolymer concrete. (30th November 2020) - Cheng, ZhengQing; Zhao, Renda; Yuan, Yuan; Li, Fuhai; Castel, Arnaud; Xu, Tengfei
Abstract: The ageing coefficient is required in the age-adjusted effective modulus method to assess the effect of creep in concrete structures subjected to varied stress history. In this paper, experiments were carried out to calibrate the ageing coefficient for early age tensile creep of blended slag and low calcium fly ash geopolymer concrete. The development of total strains of geopolymer concrete under sustained tension, including instantaneous strain, creep strain and shrinkage strain was monitored by using the dog-bone shaped specimens. The specimens were loaded at the age of 2, 3, 4, 7, 14, 21 days, respectively. The strains of the unloaded companion specimens were monitored as well. The development of the creep coefficient φ ( t, τ 0 ) for geopolymer concrete was calculated based on the experimental results. By using the step-by-step numerical analysis, the ageing coefficient for early age tensile creep of geopolymer concrete was assessed. An ageing coefficient of 0.8 is recommended for structural design. The comparison between calculated and measured tensile strains from the restrained concrete ring test shows the validity of the proposed value of the ageing coefficient.